2015
DOI: 10.5455/msm.2015.27.412-416
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Emotional Intelligence with Religious Coping and General Health of Students

Abstract: Aim:This research organized to determine the relationship between Emotional Intelligence (EI) with Religious Coping and Mental Health of students at Mazandaran University of Medical Sciences.Method:This descriptive and analytical study was conducted in 2014 on 335 students at Mazandaran University of Medical Sciences. Students were selected by stratified random sampling method. The instruments to gather data were Bradberry and Greaves Standard Emotional Intelligence Questionnaire, the 12-item General Health Qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
1
8
0
1
Order By: Relevance
“…Items with positive content are scored from 1 to 6 (never to always), while items with negative content are scored from 6 to 1 (always to never). Scores of 59, 60 -79, 80 -89, and 90 -100 show weak and worrying, weak to average, average, and high emotional intelligence, respectively (11). In the present study, the validity of the questionnaire was confirmed, based on the comments of 10 nursing experts.…”
Section: Instrumentssupporting
confidence: 57%
“…Items with positive content are scored from 1 to 6 (never to always), while items with negative content are scored from 6 to 1 (always to never). Scores of 59, 60 -79, 80 -89, and 90 -100 show weak and worrying, weak to average, average, and high emotional intelligence, respectively (11). In the present study, the validity of the questionnaire was confirmed, based on the comments of 10 nursing experts.…”
Section: Instrumentssupporting
confidence: 57%
“…This issue is very important in cancer patients due to the risk of developing stress due to various pressures which occur due to having an illness of this type (Esmaeili, Hesamzadeh, Bagheri-Nesami, & Berger, 2015;Hynes, 1996;Phelps et al, 2009). These guidelines are an intrinsic process applied by a person in the face of everyday problems (Bagheri Nesami, Goudarzian, Zarei, et al, 2015). Religious coping is one of the most important types of coping strategies, which included concepts such as trust in God (Bagheri Nesami, Goudarzian, Zarei, et al, 2015;Billings & Moos, 1984) as a method for dealing with life changing illnesses such as cancer.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Connection with God, can be a different experience in dealing with anxiety and depression, exerting positive results. [10,11] Spiritual understanding arising from people's mental health results in an awareness of facts, values, credibility and ethics. [12,13] The Quran recitation is considered as a religious coping behavior and it is of particular importance in Muslim communities.…”
Section: Introductionmentioning
confidence: 99%